(untitled) - Campbell, G. Michael (New York, 2009)
According to the Project Management Institute, over 80 percent of a project manager's job is communication yet most project management books hardly discuss it. "Communications Skills for Project Managers" provides practical advice and strategies for ensuring success, even in the face of shifting organizational priorities, constantly evolving expectations, and leadership turnover. This important guidebook gives readers the practical strategies they need to keep everyone including themselves in the loop. Even a project that is brought in on time and on budget can be considered a failure if those outside a project team haven't been clearly communicated with throughout the project lifespan. This book provides readers with the skills they need for ensured project success, every time.
Keywords: Project management,Communication in management,Quản lý dự án,Truyền thông trong quản lý